Region of interest LiDAR - Gomes, Tiago João Almeida (2020)
In this document is presented the work developed in the master thesis on "Region of Interest LiDAR". The goal is to develop a LiDAR capable of characterizing a region of interest with high precision. Taking into account the high error in a triangulation LiDAR for great distances, an ROI LiDAR could be able to complement a triangulation LiDAR, making it possible to distinguish different spots at great distances. This LiDAR is validated using a simulation tool developed in Matlab throughout the thesis, based on a system consisting of a mirror, a lens and a sensor, where all defined parameters, from lens diameter, the focal length of the lens, the distance between mirror and lens and sensor size influence the results. These values were defined through different tests so that, with the defined values, it was possible to achieve the objectives of this thesis. This work theoretically shows that a LiDAR ROI is doable and feasible, being an option to consider for the automotive industry, completing a triangular LiDAR.